Identification of the PmWEEP locus controlling weeping traits in Prunus mume through an integrated genome-wide association study and quantitative trait locus mapping. (1st June 2021) - Zhuo, Xiaokang; Zheng, Tangchun; Li, Suzhen; Zhang, Zhiyong; Zhang, Man; Zhang, Yichi; Ahmad, Sagheer; Sun, Lidan; Wang, Jia; Cheng, Tangren; Zhang, Qixiang
Abstract: Weeping Prunus mume (mei) has long been cultivated in East Asia for its specific ornamental value. However, little is known about the regulatory mechanism of the weeping trait in mei, which limits molecular breeding for the improvement of weeping-type cultivars. Here, we quantified the weeping trait in mei using nested phenotyping of 214 accessions and 342 F1 hybrids. Two major associated loci were identified from the genome-wide association study (GWAS), which was conducted using 3, 014, 409 single nucleotide polymorphisms (SNPs) derived from resequencing, and 8 QTLs and 55 epistatic loci were identified from QTL mapping using 7, 545 specific lengths amplified fragment (SLAF) markers. Notably, an overlapping PmWEEP major QTL was fine mapped within a 0.29 Mb region on chromosome 7 (Pa7), and a core SNP locus closely associated with the weeping trait was screened and validated. Furthermore, a total of 22 genes in the PmWEEP QTL region were expressed in weeping or upright mei based on RNA-seq analysis. Among them, only a novel gene ( Pm024213 ) containing a thioredoxin (Trx) domain was found to be close to the core SNP and specifically expressed in buds and branches of weeping mei. Co-expression analysis of Pm024213 showed that most of the related genes were involved in auxin and lignin biosynthesis. These findings provide insights into the regulatory mechanism of the weeping trait and effective molecular markers for molecular-assisted breeding in Prunus mume .